2008
DOI: 10.1186/1475-2875-7-137
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum variant STEVOR antigens are expressed in merozoites and possibly associated with erythrocyte invasion

Abstract: Background: Plasmodium falciparum STEVOR proteins, encoded by the multicopy stevor gene family have no known biological functions. Their expression and unique locations in different parasite life cycle stages evoke multiple functionalities. Their abundance and hypervariability support a role in antigenic variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 22 publications
5
38
0
1
Order By: Relevance
“…Interestingly, the ex vivo , non-binding parasites failed to express var , A-type rif and stevor genes whereas B-type rif and Pfmc-2TM , respectively, were found to be expressed, suggesting that the latter two gene families may encode proteins that are not targeted to the erythrocyte surface and therefore do not participate in endothelial receptor binding. Indeed, surface exposition of PfEMP-1 and recently of STEVOR has been already demonstrated [6], [21] and various studies imply that A-type RIFIN proteins are transported via the Maurer's clefts to the erythrocyte membrane [16], [19], [45]. Moreover, PfEMP-1, RIFIN and STEVOR proteins were previously determined as targets of the adaptive antibody-mediated immunity against P. falciparum malaria [6], [46], [47], suggesting exposure of these proteins at the outside of the erythrocyte membrane bilayer, where they are accessible to serum antibodies.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the ex vivo , non-binding parasites failed to express var , A-type rif and stevor genes whereas B-type rif and Pfmc-2TM , respectively, were found to be expressed, suggesting that the latter two gene families may encode proteins that are not targeted to the erythrocyte surface and therefore do not participate in endothelial receptor binding. Indeed, surface exposition of PfEMP-1 and recently of STEVOR has been already demonstrated [6], [21] and various studies imply that A-type RIFIN proteins are transported via the Maurer's clefts to the erythrocyte membrane [16], [19], [45]. Moreover, PfEMP-1, RIFIN and STEVOR proteins were previously determined as targets of the adaptive antibody-mediated immunity against P. falciparum malaria [6], [46], [47], suggesting exposure of these proteins at the outside of the erythrocyte membrane bilayer, where they are accessible to serum antibodies.…”
Section: Discussionmentioning
confidence: 98%
“…In the case of P. falciparum , the expression of RIFIN and STEVOR on the iRBC surface (Fernandez et al, 1999; Kyes et al, 1999; Niang et al, 2009) implies that they confer an important survival advantage. The expression of STEVOR in multiple parasite stages including merozoites (Blythe et al, 2008; Khattab et al, 2008; Khattab and Meri, 2011; Petter et al, 2007), sporozoites and gametocytes (McRobert et al, 2004) suggests that STEVOR mediates multiple distinct functions (Blythe et al, 2004). The observation that some synthetic peptides based on a STEVOR sequence had some RBC binding activity (Garcia et al, 2005), suggested that STEVOR could function in the invasion process by enhancing initial interaction of merozoites with RBC.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The encoded STEVOR proteins exhibit a semiconserved N-terminal domain and a central variable domain exposed on the erythrocyte surface, whereas the conserved C-terminal domain is cytoplasmic. 17,18 Besides their role in invasion, adhesion, and rosetting in asexual stages, [19][20][21][22] STEVOR proteins have been shown to impact the deformability of the infected erythrocyte in mature asexual parasites and immature sexual stages. 6,23 However, the mechanism underlying STEVOR-mediated changes in erythrocyte deformability remains unclear.…”
Section: Introductionmentioning
confidence: 99%